mutA and mutC: two mutator loci in Escherichia coli that stimulate transversions. - Michaels, M L (1990)
Two transversion-specific mutator loci, mutA and mutC, were identified in Escherichia coli. Mutators with high rates of A.T----T.A transversions were identified using a screening technique that relied upon the reversion of an altered lacZ gene back to wild-type via a specific A.T----T.A transversion. Among the mutators collected, one class mapped to a previously unidentified locus that we designate mutA. Analysis of reverse mutations in lacZ and forward nonsense mutations in lacI showed that the mutA strain has higher levels of A.T----T.A and G.C----T.A transversions, and to a lesser degree A.T----C.G transversions. The mutA locus maps very near to, but is separable from, mutL, at about 95 min on the E. coli chromosome. Both its mutagenic specificity and complementation experiments confirmed that mutA is distinct from mutL and from a nearby mutator locus, miaA. The phenotype of a mutA mutL double mutator strain suggests that the mutA gene product prevents some replication errors. Another mutator, designated mutC, maps very near uvrC, at 42 min, but is distinguishable from uvrC, which has no mutator effects. The specificity of reversion of lacZ mutations in a mutC strain is identical to that in a mutA strain. Also, the behavior of a mutC mutS double mutant is identical to that of a mutA mutL double mutant. It is likely that mutA and mutC are components of the same error-avoidance system.